Washington photometry of open cluster giants: two moderately metal-poor anticentre clusters - Parisi, Maria Celeste (2005)
New photometric data in the Washington system are presented for red giant candidates in Q1 NGC 1817 and 2251, two open clusters located towards the Galactic anticentre direction. In the case of NGC 2251, the Washington data are supplemented with new UBV and David Dunlap Observatory (DDO) photoelectric photometry. Published radial velocities are used to separate field stars from cluster giants. The photometric data yield an effective temperature and metal abundance for each cluster member. Five independent Washington abundance indices yield mean metallicities of Fe/H] = −0.33 ± 0.08 and 0.25 ± 0.04 for NGC 1817 and 2251, respectively. From combined BV and DDO data, we also derive E(B − V) = 0.21 ± 0.03 and [Fe/H]DDO = −0.14 ± 0.05 for NGC 2251. Both objects are then found to be on the metal-poor side of the distribution of open clusters, their metallicities being compatible with the existence of a radial abundance gradient in the disc. Using the WEBDA Open Cluster data base and the available literature, we re-examined the overall properties of a sample of 30 clusters located towards the Galactic anticentre with the distances, ages and metallicities available. This cluster sample presents no evidence of an abundance gradient perpendicular to the Galactic plane, nor is an age–metallicity relation found. However, a radial abundance gradient of −0.093 dex kpc−1 is derived over a Galactocentric distance of 14 kpc, a gradient which is in keeping with most recent determinations. This value practically does not change when all clusters with basic parameters known up to this date are considered.